Penerapan Teknologi Digital Platform E-Learning Dalam Pendidikan Agama Islam Pada Fase D Kelas VIII di SMP N 3 Kec. Lubuk Sikaping Kabupaten Pasaman - Irawan, Sofiyanita; Hasnah, Nur (Madani: Jurnal Ilmiah Multidisiplin, 2025)
AbstractThis research is motivated by the importance of the Application of Digital Technology Platform E Learning in Islamic Religious Education. The purpose of this study is to determine the Application of Digital Technology Platform E Learning in Islamic Religious Education in Phase D Class VIII at SMP N 3 Kec. Lubuk Sikaping Pasaman Regency. To determine the inhibiting factors for the Application of Digital Technology Platform E Learning in the Industrial Revolution 4.0 era presents significant challenges for the world of education, especially in learning Islamic Religious Education (PAI) research by making PAI teachers as key informants, curriculum representatives and students as supporting informants. Data collection techniques by conducting observations, interviews and documentation. This qualitative research aims to analyze the obstacles to the implementation of the digital e-learning platform in PAI learning for class VIII at SMP N 3 Kec., using data collection techniques through observation, interviews, and documentation. Data are analyzed using the stages of data reduction, data presentation, and drawing conclusions. The inefficiency of the learning process and the limited internet quota of students. Factors that influence the effectiveness of learning are divided into internal factors in the form of lack of student learning motivation, and external factors include the family environment and limited school facilities and infrastructure. To overcome this, PAI teachers have taken strategic steps by increasing digital literacy through workshops on introducing learning technology features, as well as utilizing affordable learning platforms such as Canva, Kahoot, and Google Form by optimizing the free features available.